The effect of vigorous continuous and interval exercise training along with resveratrol on SIRT3 and OGG1 proteins in the liver tissue of male Wistar rats - Mohammad Esmaeil Afzalpour; Hadi Sarir; Zoufa Zanjirian; Mohsen Moammadnia Ahmadi; ELHAM GHASEMI (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: Sirtuins-3 (SIRT3) is a mitochondrial deacetylase and through acetylation of Oxoguanine Glycosylase 1(OGG1) protein caused repair mitochondrial DNA damage and prevents cell apoptosis. The purpose of this study was to evaluate the effect of vigorous continuous and interval exercise training along with resveratrol on SIRT3 and OGG1 proteins in the liver tissue of male Wistar rats. Methods: In this research, forty-eight male Albino Wistar rats divided into six equal of eight groups including sedentary control, supplement, interval exercise, interval exercise + supplement, continuous training and continuous training+ supplement. Continuous and interval training performed for 6 weeks, six days per week at speed of 27 and 54 m/min respectively on a rat treadmill. Resveratrol users received daily 50 mg/kg of body weight supplements as gavage.  After intervention, the animals were anesthetized and their liver samples were analysed using one-way ANOVA and Tukey's post hoc tests. Results: After 6 weeks OGG1 level was significantly increased in continuous exercise (p=0.0001) and continuous training + supplement (p = 0.0001) groups relative to the control group. Also, liver tissue SIRT3 levels in supplementation group (p = 0.01), interval training group (p = 0.04), interval training + supplement group (p = 0.04), continuous exercise group (p = 0.001), and continuous training + supplement group (P = 0.001) increased than control group after six weeks. Conclusion: Compare to the interval training, performing of continuous training along with resveratrol consumption can induce more improvement in cell survival and life-span factors such as SIRT3 and OGG1.